Implementing the Caring Character Education Reinforcement Program through Young Red Cross Activities - Fajarwati, Retno; Triyanto, Triyanto; Hartanto, Rima Vien Permata (International Journal Labs, 2023)
The purpose of this study is to describe the obstacles to the implementation of strengthening caring character education in SMA Negeri 1 Sidoharjo. The type of research used in this study is descriptive qualitative. Data collection techniques using observation, interviews, and documentation. Data analysis consists of data reduction, data presentation, and conclusion drawing/verification. The results showed that: Youth Red Cross Extracurricular (PMR) is one of the forums for coaching and developing adolescent members with the aim of building and developing the character of members. The implementation of PMR is guided by one of the principles of Kepalang Merahan, which is to foster social attitudes, in the form of an attitude of social care through social and health activities in the school environment, family/home, and community. However, the implementation is constrained by various factors, namely: (1) the existence of inadequate facilities and infrastructure (2) activities are not well coordinated, (3) students are less enthusiastic about participating in extracurricular activities, (4) No good cooperation from the principal, teachers and students themselves, (5) there is a lack of attention to funding extracurricular activities. (6) PMR extracurricular activities are carried out in the afternoon, which means that training cannot be maximized. Apart from the existence of various obstacles, in principle, the PMR extracurricular activities carried out are activities as an effort to shape individual students to become more characterized and become good personalities and uphold the social values that exist in society.